The racial contract - Mills, Charles W. 1951-2021 (Cornell University Press, 2022)
The Racial Contract : what's old is new again -- The Racial Contract is political, moral and epistemological -- The Racial Contract is a historical actuality -- The Racial Contract is an exploitation contract -- The Racial Contract norms (and races) space -- The Racial Contract norms (and races) the individual -- The Racial Contract underwrites the modern social contract -- The Racial Contract has to be enforced through violence and ideological conditioning -- The Racial Contract historically tracks the actual moral/political consciousness of (most) white moral agents -- The Racial Contract has always been recognized by nonwhites as the real moral/political agreement to be challenged -- The "Racial Contract" as a theory is explanatorily superior to the raceless social contract
Includes bibliographical references and index
Twenty-fifth anniversary printing with new material 2022. - First edition published 1997 by Cornell University Press. - First printed in paperback 1999
Keywords: Rassismus; Ethnische Beziehungen; Sozialvertrag; Inter-Gruppenbeziehung; Ethnische Gruppe; Race relations; Racism; Social contract; White supremacy movements; Political science / Philosophy